PERBEDAAN LAMA KALA II PRIMIPARA YANG SENAM HAMIL DAN TIDAK SENAM HAMIL - Ismeili, Wenna; Suherni, Suherni; Maryani, Tri (Jurnal Kesehatan Ibu dan Anak, 2013)
Prolonged labor is one of the causes of maternal mortality in the world by 8% and 9 % in Indonesia, common especially in primipara. Second stage of labor is called critical stage because all the early predictions can be changed at all from the estimated. Power is an important factor in the delivery which can be controlled in order to delivery went smoothly. One way is by pregnancy exercise. RB Rachmi provide pregnancy exercise service. Pregnancy exercise enthusiasts decline by the end of 2012, from an average 15-25 people to 10-15 people per week. Purpose to determine the difference in second stage length of primipara whose pregnancy exercise and not. This research employed observational methods with prospective cohort design. The research was done at RB Rachmi Yogyakarta. Samples were taken by purposive sampling techniques consisting 18 people for each group, analyzed by independent t-test. The result: mean of second labor length of primipara whose pregnancy exercise is 20,56 minutes and not pregnancy exercise is 47,50 minutes with mean difference is 26,944 minutes, the result of independent t-test concerning p-value 0,0001 (<0,05). Conclusion: there is difference of a second labor length between primipara whose pregnancy exercise and not pregnancy exercise at RB Rachmi Yogyakarta in 2013.